Scattering Theory for Jacobi Operators with General Step-Like Quasiperiodic Background - Egorova, I.; Michor, J.; Teschl, G. (Журнал математичної фізики, аналізу, геометрії, 2008)
We develop direct and inverse scattering theory for Jacobi operators with step-like coefficients which are asymptotically close to different finite-gap quasiperiodic coefficients on different sides. We give a complete characterization of the scattering data, which allow unique solvability of the inverse scattering problem in the class of perturbations with finite first moment. Mathematics Subject Classification: 47B36, 81U40, 34L25, 39A11.